2015
DOI: 10.1080/00438243.2014.991803
|View full text |Cite
|
Sign up to set email alerts
|

Fascination with the tiny: social negotiation through miniatures in Hellenistic Babylonia

Abstract: The tremendous diversity and variety of miniature objects in Hellenistic Babylonia reflects a social environment of intensive cross-cultural interaction and widespread change. Considering the aspect of miniaturization itself reveals how tiny things participated in this social transformation. Through their appealing and non-threatening materiality, miniatures established an intimate connection with their users that encouraged identity sharing and illusions of power over the outside world. Miniatures of performi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The inherent symbolism of miniature vessels likely varied based on the identity of the producer, despite the shared association with ritual upon deposition. Langin-Hooper (2015:65) suggested that interactions with miniatures take on a performative quality tied to physical intimacy between the individual and the object. As noted earlier, vessels produced by novice adults or children may accrue additional significance for the family or social group.…”
Section: Discussionmentioning
confidence: 99%
“…The inherent symbolism of miniature vessels likely varied based on the identity of the producer, despite the shared association with ritual upon deposition. Langin-Hooper (2015:65) suggested that interactions with miniatures take on a performative quality tied to physical intimacy between the individual and the object. As noted earlier, vessels produced by novice adults or children may accrue additional significance for the family or social group.…”
Section: Discussionmentioning
confidence: 99%
“…The second case is represented by the study of the miniature objects in Hellenistic Babylonia (Langin-Hooper 2015). In this case, it is the cultural and social environments (the cross-cultural interaction between the Greek and Oriental worlds in the Hellenistic period) that provide points of comparison with the material of Kharayeb.…”
Section: The Role Of Dimension and The Right Distancementioning
confidence: 99%
“…The scale of objects relative to humans can be used as a way of manipulating the world (Bailey 2005); miniaturizing things is a globally widespread practice, and while it often creates objects that are dysfunctional in the physical sense (Foxhall 2015), can be used to instil a sense of mastery over them through exaggerating our scalar relationship with them, and, by extension, the wild, such as with the clay animal figurines from Neolithic Çatalhöyük, (Meskell 2015). In Hellenistic Babylonia the rendering of soldiers and deities in miniature enabled a sense of control over the often violent upheavals endemic to the region (Langin-Hooper 2015). Chin-Ying Tseng (2021, this volume) considers the Buddhist sculptures in the Five Caves of Tan Yao in Northern China, the earliest of a number of caves excavated into the Wuzhou Mountain by the ruling family of the Northern Wei dynasty (386-534 AD: in this specific case 460-5 AD).…”
Section: Scale and Attentionmentioning
confidence: 99%